Eligibility of out-of-hospital cardiac arrest patients for extracorporeal cardiopulmonary resuscitation in the United States: A geographic information system model. (November 2022) - Gottula, Adam L.; Shaw, Christopher R.; Gorder, Kari L.; Lane, Bennett H.; Latessa, Jennifer; Qi, Man; Koshoffer, Amy; Al-Araji, Rabab; Young, Wesley; Bonomo, Jordan; Langabeer, James R.; Yannopoulos, Demetris; et al.
Abstract: Background: Recent evidence suggest that extracorporeal cardiopulmonary resuscitation (ECPR) may improve survival rates for nontraumatic out-of-hospital cardiac arrest (OHCA). Eligibility criteria for ECPR are often based on patient age, clinical variables, and facility capabilities. Expanding access to ECPR across the U.S. requires a better understanding of how these factors interact with transport time to ECPR centers. Methods: We constructed a Geographic Information System (GIS) model to estimate the number of ECPR candidates in the U.S. We utilized a Resuscitation Outcome Consortium (ROC) database to model time-dependent rates of ECPR eligibility and the Cardiac Arrest Registry to Enhance Survival (CARES) registry to determine the total number of OHCA patients who meet pre-specified ECPR criteria within designated transportation times. The combined model was used to estimate the total number of ECPR candidates. Results: There were 588, 203 OHCA patients in the CARES registry from 2013 to 2020. After applying clinical eligibility criteria, 22, 104 (3.76%) OHCA patients were deemed eligible for ECPR. The rate of ROSC increased with longer resuscitation time, which resulted in fewer ECPR candidates. The proportion of OHCA patients eligible for ECPR increased with older age cutoffs. Only 1.68% (9, 889/588, 203) of OHCA patients in the U.S. were eligible for ECPR based on a 45-minute transportation time to an ECMO-ready center model. Conclusions: Less than 2% of OHCA patients are eligible for ECPR in the U.S. GIS models can identify the impact of clinical criteria, transportation time, and hospital capabilities on ECPR eligibility to inform future implementation strategies.